Impact of sorafenib dosing on outcome from the European patient subset of the GIDEON study. (September 2015) - Daniele, Bruno; Croitoru, Adina; Papandreou, Christos; Bronowicki, Jean-Pierre; Mathurin, Philippe; Serejo, Fatima; Stål, Per; Turnes, Juan; Ratziu, Vlad; Bodoky, György
SUMMARY : Aims: To evaluate sorafenib dosing and safety in the Global Investigation of therapeutic GIDEON study's European subpopulation.Patients & methods: Patient demographics, disease characteristics and treatment history were recorded at enrollment; dose, adverse events and efficacy were recorded at follow-up.Results: Of 1113 evaluable patients, 82% started on 800 mg/day sorafenib; patients starting on 400 mg/day were slightly older, had baseline characteristics indicative of greater disease progression and higher adverse events incidences (96 vs 88%). Treatment duration (18.0 vs 13.0 weeks) and median overall survival (12.1 vs 9.4 months) were longer in patients receiving 800 mg/day.Conclusion: Imbalances in independent predictive factors may have led to longer survival in patients receiving 800 mg/day sorafenib; nonetheless, results suggest that the majority can start on this dose.